The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0103103
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-Day- and Light-Dependent Expression of Ubiquitin Protein Ligase E3 Component N-Recognin 4 (UBR4) in the Suprachiasmatic Nucleus Circadian Clock

Abstract: Circadian rhythms of behavior and physiology are driven by the biological clock that operates endogenously but can also be entrained to the light-dark cycle of the environment. In mammals, the master circadian pacemaker is located in the suprachiasmatic nucleus (SCN), which is composed of individual cellular oscillators that are driven by a set of core clock genes interacting in transcriptional/translational feedback loops. Light signals can trigger molecular events in the SCN that ultimately impact on the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…UBR4 and POE are broadly expressed in the murine and fly brains, including virtually all SCN neurons and the PDF-positive LN v s [170]. A prior study demonstrated that the abundance of UBR4 in the SCN is both rhythmic and light-inducible, suggesting that it may regulate clock-timing processes or photic entrainment [171]. However, ablating Ubr4 in all GABAergic neurons, and thus all SCN neurons, has no effect on free-running rhythms under DD or light-induced phase delays in mice [170].…”
Section: The Roles Of N-recognins In Circadian Rhythmsmentioning
confidence: 99%
See 1 more Smart Citation
“…UBR4 and POE are broadly expressed in the murine and fly brains, including virtually all SCN neurons and the PDF-positive LN v s [170]. A prior study demonstrated that the abundance of UBR4 in the SCN is both rhythmic and light-inducible, suggesting that it may regulate clock-timing processes or photic entrainment [171]. However, ablating Ubr4 in all GABAergic neurons, and thus all SCN neurons, has no effect on free-running rhythms under DD or light-induced phase delays in mice [170].…”
Section: The Roles Of N-recognins In Circadian Rhythmsmentioning
confidence: 99%
“…In terms of N-recognins, only UBR1 and UBR4 have been implicated in the regulation of circadian rhythms [170][171][172]. In the case of UBR1, it was shown to induce the degradation of CONIDIAL SEPARATION 1 (CSP1), a Neurospora protein whose presence in the morning represses the transcription of evening-specific genes [172].…”
Section: The Roles Of N-recognins In Circadian Rhythmsmentioning
confidence: 99%
“…Ubiquitin protein ligase E3 component N‐recognin 4 (UBR4) is an E3 ligase of the N‐end rule pathway with a potential role in PER2 ubiquitination and degradation. UBR4 protein peaks with a phase that coincides with the beginning of PER2 degradation in the SCN (early night) (Ling et al., 2014). More research will be needed to define the implication of this ubiquitin ligase in clock function.…”
Section: Ubiquitination and Deubiquitination In The Clock Of Mammalsmentioning
confidence: 99%
“…Up to now, research on UBR4 has mainly focused on the nervous system ( 5 7 ). Interestingly, the number of Drosophila pupae decreased after Ubr4 gene knockdown in our preliminary experiments, suggesting that Ubr4 may be related to reproductive capacity.…”
Section: Introductionmentioning
confidence: 99%